Congenital Visceral Malformations in Children with Down Syndrome (DS) Followed in the Pediatric Unit of the CNHU, Cotonou, Bénin - ADJAGBA, MAHOUNA PHILIPPE DOTOU; ALAO MAROUFOU, MODJÉRÉ OLA MAROUFOU JULES; YEKPE ÉPSE AHOUANSOU, HERMIONE PATRICIA FRIDA (My University, 2017)
Introduction: Mortality in Down syndrome (DS) remain high and often in relation with visceral malformations. The aim of this work was to describe the congenital visceral malformations associated with DS in children followed in the pediatric unit of National Health Teaching Hospital of Cotonou, in order to improve their management. Patients and methods: It was a prospective and descriptive survey conducted on children who were treated for DS at the pediatric unit of the National Health Teaching Hospital of Cotonou from October 2015 through July 2016. All children had a diagnosis of DS based on karyotype with trisomy 21 and underwent heart, gastrointestinal and kidney ultrasonographies. Results: A total of 36 children were included. The sex ratio was 1.25 and infants under 12 months were the most represented age group (55.56 %). The mean age at diagnosis was 18.8 months. The majority of mothers were aged than 35 years. Clinical features were dominated by up slanting palpebral fissures and hypertelorism. The visceral malformations were observed only in heart with a frequency of 55.55%. Atrio-ventricular septal defect (27.78%) and patent ductus arteriosus (16.76%) were predominant. Nondisjunction trisomy 21 was found in all children. Conclusion: Congenital visceral malformations associated to DS in children at pediatric unit of the National Health Teaching Hospital of Cotonou were exclusively cardiac with atrioventricular septal defect as major type. Early diagnosis of DS with malformations screening are essential for better management of affected children.
Keywords: Down syndrome; Birth defect; Congenital heart disease; Gastrointestinal malformation; Kidney malformation